Report of an Endemic Ceylonese Grass from India - Singh, N. P.; Deshpande, U. R. (Indian Forester, 1973)
lsaehne globosa (Thunb.) O. Ktze. var. effusa (Trim. ex Hook. f.) Senaratna, a grass so far endemic to Sri Lanka, is being reported for the first time from the Union Territory of Goa in India.